Bilateral Necrotizing Herpes Simplex Keratitis in an Immunocompetent Patient With Genetic Analysis of Herpes Simplex Virus 1. Issue 9 (September 2019) - Yoshida, Masaaki; Hosogai, Mayumi; Yokokura, Shunji; Sato, Kota; Hariya, Takehiro; Kobayashi, Wataru; Okabe, Tatsu; Todokoro, Daisuke; Nakazawa, Toru
Abstract : Purpose: To report a case of severe bilateral necrotizing herpes simplex keratitis (HSK) in an immunocompetent patient, with genotyping of the underlying herpes simplex virus 1 (HSV-1). Methods: Genetic analyses of HSV-1 in tear samples were performed with polymerase chain reaction-based restriction fragment length polymorphism, targeting the viral genes unique short (US)2, US4 (glycoprotein G), and US7 (glycoprotein I). Results: A 64-year-old woman with no history of atopy or immune disorders manifested bilateral keratitis with geographic ulcer. Her initial visual acuity was 20/1000 (OD) and 20/20 (OS). Polymerase chain reaction testing of a tear sample revealed the presence of HSV-1 in both eyes, and the patient was diagnosed with bilateral HSK. Both eyes progressed to necrotizing keratitis during the treatment course. Continuous intensive treatment, at first with acyclovir ointment and oral valacyclovir and later with steroid eye drops for stromal keratitis, finally improved the patient's condition. However, after 2 years, her visual acuity was limited to 20/250 (OD) and 20/60 (OS) because of corneal opacity from scarring. We found that the strain in the current case had a genotype combination of C/A/B (for US2/US4/US7), a known pattern in Japan, in both eyes. Conclusions: We successfully performed an unprecedented genetic analysis of an HSV-1 strain isolated from a case of bilateral necrotizing HSK in an immunocompetent patient. The association of the HSV-1 genotype with the clinical manifestation remains unclear, calling for more data from new cases, especially from different geographic regions. Abstract : Supplemental Digital Content is Available in the Text.